Distribution of ionic components between two immiscible solutions. Partition of weak bases - Garcia, Julia Ines (2010)
Theoretical aspects concerning the calculation of the distribution potential at the interface between two immiscible electrolyte solutions are examined. In particular, we analyze the effect of the ratio between the volumes of each phase (r) on the distribution potential for several systems with different levels of complexity. First, we examine the effect of water autoprotolysis for a system composed of completely dissociated electrolytes and weak bases. Finally, the effect of including the ion-pair formation on the potential distribution is considered. In all cases, the algebraic expressions for the equilibrium distribution potential, at r → 0 and at r → ∞, are developed. The results presented in this work are of fundamental importance for gaining further understanding of the basic properties of the partition of weak bases, with direct application in drug partitions, and in the theoretical treatments of ion-selective electrodes and of liquid extraction.